Incorportion of Sludges from aWater Treatment Plant in Cement Mortars - Esteves, A. (2004)
The results of the characterization of the sludge from a Portuguese water treatment plant and their leachates are presented. Dewatered sludge contains basically water, calcium, aluminium and silica, with an organic matter content of about 6%. The mineralogical constituents present in heated sludge are mainly calcite and clay minerals. Gibbsite is present only in the sludge heated at 105ºC and calcium aluminate and calcium oxide are only present in the sample heated at 700ºC. Thermal treatment does not remove the entire polymer and coagulant initially within the sludge. Sludges dewatered or heated at 105ºC inhibit the setting and hardening of the paste and the mortar so, and incorporation in mortars it is only feasible after treatment of the sludges at not less then 450ºC with an increase of the initial setting time but a decrease of the mechanical strength.